PREFERENSI EKOLOGIS JENIS-JENIS TUMBUHAN DOMINAN DI GUNUNG ENDUT, BANTEN - Sambas, EN.; Kusmana, C.; Prasetyo, LB.; Partomihardjo, T. (JURNAL BIOLOGI INDONESIA, 2013)
Thirteen plant species of main vegetation alliances were detected upon their preferences on various abiotic factors,among them, six species had preferences on either soil or topographical factors, while four species only had preferenceson soil factors, and one species only on topographical ones. On topographical factors, there were six specieshad preferences most on average elevation and one species on minimum elevation of the research plots.Keywords : dominant plant species, ecological preferences, Mount Endut